The relation between non invasive markers and using the Fibrotic index in liver biopsy specimen, from hepatitis c Patients, at Hospital Alor Star - Razul Md Nazrl, Md Kassim (2007)
Background Liver biopsy is a mandatory procedure in the management of patients with hepatitis C virus infection, especially for staging fibrosis. We aimed, in our cross sectional study, to assess the relation of the serum biochemical markers for the diagnosis of clinically significant fibrosis(inc1uding early stages). Method We assessed liver biopsy patients with detectable hepatitis C by PCR, for eligibility and took their blood sample for the biochemical test. The analysis was done on 60 patients. We devised a fibrosis index that included the most informative markers (combined With age and sex). Eleven serum markers were assessed as well as fibrosis stages: 80= no fibrosis, 81 =fibrous expansion of some portal tracts ± short fibrous septa, S2=fibrous expansion of most portal tracts ± short fibrous septa, 83= fibrous expansion of most portal areas with occasional portal to portal (PP) bridging, 84=fibrous expansion of portal areas with marked bridging ( PP as well as portal-central (PC), SS= marked bridging (pP and or PC) with occasional nodules (incomplete cirrhosis), 86= cirrhosis, probable or definite. Statistical analysis was done using mann whitney U test and receiver operating characteristics ( ROC) curves. xi RESULTS Mean value of ALT, GMT, aldosterone, HOL, and albumin with mild fibrosis and severe fibrosis, was 82±4and 125±31,47.5±31 and 81±25, 116.6±56and 184± 43,1.4± 0.3 and 0.9 ± 0.2 and, 42 ± 4 and 35 ± 3.2, respectively with a significant difference between them was (p <0.05). The area under the operating receiver characteristics showed significant accuracy for each biochemical parameters.